2016
DOI: 10.1051/matecconf/20178701004
|View full text |Cite
|
Sign up to set email alerts
|

1D Compressibility of DMS Treated With Cement-GGBS Blend

Abstract: Abstract. Great quantities of dredged marine soils (DMS) have been produced from the maintenance of channels, anchorages and for harbour development. DMS have the potential to pose ecological and human health risks and it is also considered as a geowaste. Malaysia is moving towards the sustainability approach and one of the key factors to achieve it is to reduce waste. Thus, this geowaste should be generated as a new resource to substitute soil for civil works such as for land reclamation and backfilling. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Unary binders of GGBS and CKD were prepared for comparison purposes. The replacement levels were considered adequate for good coverage for investigation and evaluation purposes per Kaliannan et al (2017), who used a similar replacement in their work on mixtures made from GGBS and cement.…”
Section: Experimental Designmentioning
confidence: 99%
“…Unary binders of GGBS and CKD were prepared for comparison purposes. The replacement levels were considered adequate for good coverage for investigation and evaluation purposes per Kaliannan et al (2017), who used a similar replacement in their work on mixtures made from GGBS and cement.…”
Section: Experimental Designmentioning
confidence: 99%
“…Mansour et al (2015) [14] conducted study on stabilized Egyptian soft soil and reported that Mv decreased as the cement content and applied stress increased. Suaathi Kaliannan et al (2017) [16] also conducted a study on solidified DMS and found that Mv decreased significantly with vertical stress increment however, the rate slowed down as the binder content increased. It can be concluded that All specimens are considered very high compressible except 15K which is considered as just high compressible.…”
Section: Fig 4: Relationship Between Yield Stress and Cement Contentmentioning
confidence: 99%
“…Wang et al (2017) indicated that MgO can be used in the stabilization of marine soils with satisfactory compressibility. The work of Kaliannan et al (2017) used cement-GGBS blend in the stabilization of dredged materials, and found that GGBS replacement is efficient in enhancing the geotechnical properties of the stabilized dredged materials. However, it was also indicated in this study that GGBS cannot be used alone in soil improvement.…”
Section: Compressibility and Permeability Of Stabilized Clay Slurrymentioning
confidence: 99%